2014
DOI: 10.1007/s11515-014-1325-z
|View full text |Cite
|
Sign up to set email alerts
|

dsRNA binding protein PACT/RAX in gene silencing, development and diseases

Abstract: PACT (Protein kinase, interferon-inducible double stranded RNA dependent activator) and its murine ortholog RAX (PKR-associated protein X) were originally identified as a protein activator for the dsRNA-dependent, interferon-inducible protein kinase (PKR). Endogenous PACT/RAX activates PKR in response to diverse stress signals such as serum starvation, and peroxide or arsenite treatment. PACT/RAX heterodimerized with PKR and activated it with its third motif in the absence of dsRNA. The activation of PKR leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In addition to activating PKR in response to cellular stress, PACT is known to function in the RNAi (44) and innate immune pathways (45), and it is possible that the P222L mutation could affect these pathways. Although our research certainly does not rule out this possibility, it definitely establishes that at least one pathway regulated by the PACT-PKR interaction is significantly altered by the P222L mutation and results in major changes in the cell survival in response to the ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating PKR in response to cellular stress, PACT is known to function in the RNAi (44) and innate immune pathways (45), and it is possible that the P222L mutation could affect these pathways. Although our research certainly does not rule out this possibility, it definitely establishes that at least one pathway regulated by the PACT-PKR interaction is significantly altered by the P222L mutation and results in major changes in the cell survival in response to the ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…PACT has been identified as a protein activator of PKR, and PACT-mediated PKR activation plays an important role in stress responses through regulating transcription, translation, apoptosis, and other essential cellular processes 62 . For decades, efforts have been made to understand the cancer-specific regulation of PACT-PKR cascade 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides dsRNA, endoplasmic reticulum (ER) stress, mechanical stress, high‐fat diet, pathogens, environmental stress, haeme limitation, cytokines (TNF‐α, IL‐1β) and irradiation also possess the ability to activate PKR . In addition, researchers have found that the PACT is a plausible cellular activator of PKR which can cause the PKR phosphorylation , while others have demonstrated that protein kinase R (PKR)‐associated protein X (RAX), murine counterpart for PACT , is accountable for the activation of PKR at cellular level, when stimulated by any extracellular stress stimuli . Table shows the list of some PKR activators that are associated with the substrate phosphorylation and physiological process linked with substrate phosphorylation.…”
Section: Pkr: Structure and Functionmentioning
confidence: 99%
“…Arsenite, thapsigargin and H 2 O 2 are well chemical inducers of stress. These inducers cause rapid phosphorylation of RAX followed by subsequent interaction of RAX with PKR leading to PKR activation, and ultimately, they cause inhibition of protein synthesis . It has been reported that the serine 18 phosphorylation is responsible for inducing conformational changes in RAX/PACT which is required for the association of dsRBM with PKR and successive PKR activation .…”
Section: Pkr: Structure and Functionmentioning
confidence: 99%